Availability, Use, and Satisfaction of Personal Protective Equipment Among Healthcare Workers: A Cross-Sectional Assessment of Low- and Middle-Income Countries. Issue 11 (November 2020) - Sarfraz, Azza; Sarfraz, Zouina; Anwer, Ammar; Sarfraz, Muzna; Siddiq, Javaria
Abstract : Objective: To assess the discrepancy among and within low- and middle-income countries (LMICs) regarding PPE availability, use, and satisfaction. Methods: The study population consisted of healthcare workers from LMICs who partook in the questionnaire survey from March 1, 2020, until April 15, 2020. Results: In the bivariate analysis, gender ( P  = 0.05), HCWs ( P  < 0.01), and level of care ( P  < 0.01) were associated with the public or private sector ( P  < 0.05). Using multivariate analysis, PPE factors were associated with the health sector ( p  < 0.05). The multivariate logistic regression model determined a Pearson's χ 2 value of 706.736 ( df  = 726, P  = −0.689) and a c-statistic of 0.592, indicating a good model. Conclusion: In LMICs, huge discrepancies are present in PPE provision to HCWs, especially among the public healthcare sectors. Efforts at national and international levels ought to be addressed to protect frontline HCWs at higher risk of contracting COVID-19. Abstract : Supplemental Digital Content is available in the text